Periodontitis in the United States: Beyond Black and White - Luisa N. Borrell, DDS, PhD, MPH; Brian A. Burt, BDS, MPH, PhD; Brenda W. Gillespie, MS, PhD (Blackwell Synergy, 2002)
This paper examines whether historical disparities in periodontal status between African Americans and whites in the United States have increased, decreased, or remained the same over the 15-year period between the First National Health and Nutrition Examination Survey (NHANES I, 1971-74) and the Third National Health and Nutrition Examination Survey (NHANES 111, 1988-94)